NECROTIZING SKIN AND SOFT-TISSUE INFECTIONS: CURRENT STATUS. A CASE-BASED REVIEW - Vashchuk, Vsevolod; Kyryk, Taras; Kulyaba, Nazar; Kulyaba, Oleg; Kushnirchuk, Mykola (Eastern Ukrainian Medical Journal, 2024)
Necrotizing skin and soft-tissue infections (NSTI) is an urgent surgical pathology. NSTI are potentially life-threatening and disabling infections. It has an insidious onset, rapid onset of symptoms, and a high fatality rate. Objectives: to review all aspects of care for patients with NSTI; to present one’s own clinical observations on the results of treatment of patients with NSTI. Materials and methods. We applied information, bibliographic and analytical methods of analysis and search in international medical information electronic databases, data of our own results of implementation of modern diagnostic algorithms and search for current clinical guidelines for the treatment of the specified group of patients with NSTI. Results. The main reasons for the unsatisfactory clinical results of treatment of patients with NSTI are: late diagnosis due to atypical symptoms of the disease and the lack of unambiguous manifestations of NSTI in the early stages of the disease. Qualified clinicians experienced in the diagnosis and treatment of NSTI can make full use of NSTI early diagnosis tests. Scales for early diagnosis of NSTI are based on general clinical non-specific laboratory markers. We presented the main views on epidemiological, clinical and laboratory NSTI; modern treatment algorithms are critically analyzed and personal experience of clinical work with the case of NSTI is presented. Also, the authors identified promising directions for further research based on an objective assessment of the advantages and disadvantages of various methods of diagnosis and treatment of NSTI. Conclusions. NSTI is an actual problem of modern surgery soft tissue infections. NSTI is characterized by a tendency to generalization, hyporeactive manifestations in patients and polyresistant polymicrobial etiology. Immunosuppressive status often occurs in patients with NSTI. Early diagnosis, urgent antibacterial therapy, aggressive surgical treatment, joint work of surgeons and intensive care physicians are the cornerstone for achieving positive clinical results in NSTI. Prediction scales (LRINEC, SIARI, Wall) are important components of early diagnosis of NSTI. These scales should be used with caution in the decision-making process. Ultimately, the diagnosis of NSTI is determined by the surgeon’s awareness and ability to perform early intervention. Adequate surgical intervention and adequate antibiotic therapy can reduce the mortality rate in NSTI.